A single-arm study to evaluate the transfer of drospirenone to breast milk after reaching steady state, following oral administration of 4 mg drospirenone in healthy lactating female volunteers - Melka, Dace (Womens Health (Lond), 2020)
OBJECTIVE: The primary objective of this trial was to assess the transfer of drospirenone to breast milk after daily administration of an oral test preparation containing 4 mg of drospirenone at the steady state. The secondary objective of the trial was to assess safety based on clinical and laboratory measurements and reporting of adverse events and/or adverse drug reactions. PATIENTS AND METHODS: This was an open label, non-comparative single-center study. Drospirenone 4 mg per day was the first postpartum contraceptive for the study participants who were no longer breastfeeding yet were still lactating. It was administered for 7 days to achieve steady-state concentration. All participants were volunteers who planned to use oral contraceptives as their family planning method in the future. RESULTS: Twelve volunteers completed the trial according to the protocol, and the samples of all 12 study completers were analyzed. The average concentration–time curve of drospirenone in plasma 24 h after the administration of the last dose (area under the curve (0–24 h)) was 635.33 ng h/mL and 120 h after the single repeated dose administration (area under the curve (0–120 h)) was 1180.57 ng h/mL, respectively. The average C(max) was 48.64 ng/mL. The average concentration–time curve of drospirenone in milk 24 h after the administration of the last dose (area under the curve (0–24 h)) was 134.35 ng h/mL and 120 h after the single repeated dose administration (area under the curve (0–120 h)) was 227.17 ng h/mL, respectively. The average C(max) was 10.34 ng/mL. CONCLUSION: On average, 18.13% of plasma drospirenone made it to breast milk and the highest concentration of drospirenone in breast milk was 17.55% of that in plasma. The total quantity of drospirenone passing to breast milk is on average 4478 ng during a 24-h period representing 0.11% of the maternal daily dose. Thus, at the recommended doses, no effects on breastfed newborns/infants are anticipated with drospirenone 4 mg.